Female Sexual Function and Dysfunction - Costantini, Elisabetta; Villari, Donata; Filocamo, Maria Teresa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses all aspects of sexuality in women and in particular explores sexual function and dysfunction in a variety of settings, including the different stages of life and a wide range of major diseases and local conditions. The aim is to refocus attention on the needs and sexual realities of women, providing a fresh point of view that will assist gynecologists, sexual medicine physicians, and urologists in delivery of high-quality care and help women themselves to understand and address sexual problems relating to desire, arousal, orgasm, and sexual pain. Psychological aspects of female sexuality and the impacts of the aging process, pregnancy, and childbirth are carefully examined. Extensive consideration is then given to the effects on sexual function of such conditions as cardiovascular disease, cancer, diabetes, neurological disease, endometriosis, pelvic organ prolapse, urinary incontinence, reproductive disorders, sexual abuse, and drug abuse. Issues of sexual identity and female dysmorphophobias are also considered. The authors are all experts in the field and have a deep understanding of the complexities of female sexuality. .
Sociocultural Considerations -- Anatomical and physiological description of women sexuality -- Female Sexuality: a state of mind -- Evaluation Systems of female sexual function -- Women's sexuality across the different stages of reproductive life -- Endometriosis and Sexuality -- POP and impact of surgery on female sexual life -- Urinary incontinence and Mid-urethral slings: which is the impact on female sexuality? -- Female Sexual life during malignancies -- Sexuality in couple with reproductive difficulties -- Sexuality after abuse -- Female sexual dysfunction in alcohol and drug abuse -- Female sexual function during male sexual dysfunction and vice versa -- Female sexuality in chronic pelvic pain -- Female Sexual Function and Neurological disease -- Female Genital Cosmetic Surgery -- Role of physical therapy in the treatment of Female Dysfunction.
Keywords: Medicine; Gynecology; Urology; Medicine & Public Health; Gynecology; Urology